2018
DOI: 10.1111/cen.13554
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin sensitivity and secretion in prediabetic patients with adrenal insufficiency on dual‐release hydrocortisone treatment: a 36‐month retrospective analysis

Abstract: Long-term DR-HC therapy is associated with an improvement in insulin secretion and sensitivity in patients with prediabetes. However, all patients appear to benefit from the treatment in terms of improvement of metabolic and anthropometric parameters. Larger studies are required to confirm our preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
1
39
0
2
Order By: Relevance
“…Several studies have shown that DR-HC treatment is associated with a reduction in weight, WC, systolic and diastolic blood pressure, HbA1c and lipids and an improvement of quality of life (6, 7, 9, 15). Furthermore, a recent study by our group documented a decrease in BMI, WC, HbA1c and an increase in HDL-C in patients treated with DR-HC for 36 months, showing a significant improvement in insulin secretion and sensitivity, even in patients with pre-diabetes (8).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Several studies have shown that DR-HC treatment is associated with a reduction in weight, WC, systolic and diastolic blood pressure, HbA1c and lipids and an improvement of quality of life (6, 7, 9, 15). Furthermore, a recent study by our group documented a decrease in BMI, WC, HbA1c and an increase in HDL-C in patients treated with DR-HC for 36 months, showing a significant improvement in insulin secretion and sensitivity, even in patients with pre-diabetes (8).…”
Section: Discussionmentioning
confidence: 77%
“…It is characterized by an immediate-release fraction of HC in the outer layer of the tablet and an extended-release fraction in the core, able to provide an adequate concentration of cortisol within 50 min of administration, half-cortisol plasma concentration for 6 h thereafter and a minimal cortisol level 18–24 hours after intake (4). This characteristic formulation has been shown to improve anthropometric and metabolic parameters and quality of life, appearing to be safe in the long term (5, 6, 7, 8, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…13 DR-HC has been reported to improve anthropometric and metabolic parameters, appearing to be safe even in the long term. 1419…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in pre-diabetic patients only a significant decrease in insulinemia ( p = 0.014), AUC 2hinsulinemia ( p = 0.038) and VAI ( p = 0.001), in concomitance with a significant increase in the oral disposition index (DIo; p = 0.041) and Matsuda index of insulin sensitivity (ISI-Matsuda; p = 0.038) were observed. No differences in metabolic parameters, insulin secretion and sensitivity index were found comparing PAI and SAI patients ( 56 ).…”
Section: Glycometabolic Effects Of Gc Replacement Therapymentioning
confidence: 88%